Quantification of solubility trapping in natural and engineered CO2 reservoirs. Issue 4 (2021) - Leslie, Rory; Cavanagh, Andrew J.; Haszeldine, R. Stuart; Johnson, Gareth; Gilfillan, Stuart M. V.
No abstract available